Right Atrial Myxoma: Unusual Location; Uncommon Association - Sanjeev, Om Prakash (Ann Card Anaesth, 2018)
We are presenting a case of the right atrial myxoma found in a case of rheumatic heart disease. During transthoracic echocardiography for the evaluation of a suspected rheumatic valvular heart disease, a diagnosis of severe mitral stenosis with severe mitral regurgitation with the right atrial thrombus was made. On transesophageal echocardiography, a pedunculated mass in the right atrium was confirmed. In the course of surgery, it was found that there is a tumor originating from the right atrial appendage (RAA) which was confused with clot on echocardiography. Rheumatic heart disease and myxomas have different etiopathogenesis, and this coexistence has not been reported. Further, right atrial myxoma arising out of RAA is also being reported for the first time.